EVALUASI PEMBELAJARAN BERBASIS QUIZIZZ DI MTs NW 2 KEMBANG KERANG SEBAGAI UPAYA MENYONGSONG KURIKULUM MERDEKA - zarkasi, Taqiudin; Haris, Munawir; Muslihatun, Muslihatun; Fajri, Masriatul; Jamaluddin, Jamaluddin (Empowerment: Jurnal Pengabdian pada Masyarakat, 2023)
The Covid-19 pandemic period has ended, this is marked by learning that can be carried out face-to-face, but the impact of the pandemic is still very much felt, especially in the enthusiasm and interest in learning of students, not a few students are still unable to restore motivation and enthusiasm for learning, so the results of exams or tests have decreased, learning in class VIII MTs NW 2 Kembang Kerang has carried out face-to-face learning. So that the learning process is not boring educators prepare learning media that are interesting, creative and able to train students' concentration. In class VIII educators use the quizizz application as a learning medium. It turns out that the use of the quizizz application in class VIII has already been used during distance learning. In the field of education, Indonesia should be more advanced following technological developments or the industrial revolution 4.0. In this study the problem to be discussed is the use of the quizizz application in evaluation learning in class VIII. From the results of the study, students were very enthusiastic in working on questions and were able to train students' cognitive and concentration in answering questions, increasing learning outcomes.